Pergeseran Makna dan Tujuan Pembacaan Burdah di Desa Jaddung, Pragaan, Sumenep - Maghfur M Ramin (Living Islam: Journal of Islamic Discourses, 2018)
The narration of Burdah reading became a feature of understanding in the religious life of the Jaddung community, Pragaan, Sumenep, Madura, East Java. In the Burdah reading has been a displacement meaning, from praise and expressions of love to the Prophet to the treatment of people who feel pain. Religious rituals and their behavior indicate a deviation in their religious understanding. This has even led to the sacredness of hope for life or death. The anxiety shows the process of changing or shifting the meaning of the Burdah tradition from praise to treatment. This happened because of the construction of people's knowledge to respond to the out- break of Ta'on disease in the 1960s, sick without cause in the 1970s, and people who had long been seriously ill in the 1980s. When awareness of health and knowledge develops as it is today, the tradition of Burdah reading continues to be a theological conviction to understand about life's hopes or hopes about reality regarding death. This reality encourages the writer to examine it more seriously with Gadamer's Hermeneutic analysis. The focus of this study leads to the existence of the Burdah tradition, understanding narration, and the theology of community expectations of Jaddung, Pragaan, Sumenep, East Java.